ANALYZING INVESTMENT PATTERNS AMONG SPECIAL ECONOMIC ZONE (SEZ)-AFFECTED FARMERS IN KHED-SHERUR TALUKA OF PUNE DISTRICT - Khalate, Santosh B.; More, Dhiresh A.; Prajapati, Pooja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Special Economic Zones can boost economic activity, enhance exports, generate foreign exchange and create employment. The establishment of Special Economic Zones (SEZs) has significantly altered the socio-economic landscape of rural India, often impacting the livelihood strategies of affected communities. However the implementation of SEZs often involves acquisition of agricultural land, which has a direct impact on rural communities, particularly farmers. This study analyzes the investment patterns of SEZ-affected farmers in the Khed-Sherur Taluka of Pune District, Maharashtra, where agricultural lands have been acquired for SEZ development. When land is acquired for SEZs, many farmers lose their agricultural land and receive compensation. This research aims to understand how these farmers use the compensation money and how their investment habits have changed over time. The paper highlights the need for financial education and support systems to help farmers make better use of the compensation money and secure their livelihoods in the long term.